A General Assessment of the End-Pleistocene Chipped Stone Finds in the Drilling Trench of the Girmeler Settlement - Demir, Kerem (Fırat University, 2025)
In 2020-21, in a 1.5x2.5 meter drilling trench opened at the base of the probably destroyed mound in front of Cave “A” in Girmeler, a rocky hill on the shores of Eşen Valley in Seydikemer District of Muğla, reached layers dated to the end of the Pleistocene Period, between 12,036-10,677 BC according to radiocarbon dates. Very little research has been done on the end of the Pleistocene Period in Anatolia. However, Anatolia has the potential to find answers to many questions about the period with its location between two large cultural regions. For this reason, it is important to conduct a techno-typological analysis of the end-of-Pleistocene Period chipped stone artifacts in Girmeler Cave Mound located in the southwestern corner of Anatolia and present them to the literature. When the Girmeler, Karain B in Antalya Katran Mountain, Öküzini Cave, Kızılin Cave, Beldibi rock shelter in Kemer District and Pınarbaşı and Gedikkaya chipped stone assemblages in central Anatolia are examined, it is seen that they share the same industrial tradition.

Muğla’nın Seydikemer İlçesi’nde, Eşen Vadisi kıyısında kayalık bir tepede, iki galerili mağara (A ve B Mağaraları) ve önlerinde düzleştirilerek tahrip edilmiş bir höyükten oluşan Girmeler’de, 2020-21 yıllarında “A” Mağarasının önünde muhtemelen tahrip edilmiş höyüğün tabanına açılan 1,5x2,5 metrelik bir sondaj açmasında Pleistosen Dönem sonuna, radyokarbon tarihlerine göre MÖ 12.036-10.677 yılları arasına tarihlendirilen tabakalara ulaşılmıştır. Anadolu’da Pleistosen Dönem sonu ile ilgili çok az araştırma yapılmış bu çalışma bu alana katkı sağlaması hedeflenmektedir. Ancak Anadolu, iki büyük kültürel bölge arasında yer alan konumuyla dönemle ilgili pek çok sorunsalın cevabının bulunabileceği bir potansiyeldedir. İşte bu yüzden Anadolu’nun güney batı köşesinde yer alan Girmeler Mağarası Höyüğü Pleistosen Dönem sonu yontmataş eserlerinin tekno-tipolojik analizinin yapılarak literatüre sunulması önemlidir. Girmeler, Antalya Katran Dağı’nda yer alan Karain B, Öküzini Mağarası, Kızılin Mağarası ve Kemer İlçesi’nde yer alan Beldibi kaya sığınağı ve orta Anadolu’da yer alan Pınarbaşı ve Gedikkaya yontmataş buluntu toplulukları incelendiğinde bunların aynı endüstriyel geleneği paylaştıkları görülüyor.
Girmeler Yerleşmesi Sondaj Açması Pleistosen Sonu Yontmataş Buluntularının Genel Bir Değerlendirmesi
Keywords: Archaeological Science; Arkeoloji Bilimi; Neolithic Age Archeology; Neolitik Çağ Arkeolojisi